EFFECTIVENESS BOOK SMART MEDIA IN INCREASING AWARENESS MANAGEMENT OF DIABETES MELLITUS DIABETES MELLITUS PATIENTS IN PUSKESMAS KEDUNGMUNDU SEMARANG - jayaningrum, Fitri (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2016)
The prevalence of diabetes in Indonesia in 2013 was 2.1%. This figure is higher than in 2007 (1.1%). A total of 31 Provinces (93.9%) showing a rise in the prevalence of diabetes is significant. 2007 to 1.2% in 2013. Results Health Research (Riskesdas) in 2007 showed that the proportion of causes of death from diabetes in the age group 45-54 years in urban areas ranks into two, namely 14.7%, while in the area rural, DM ranks sixth namely 5.8%. The type of quasi-experimental research (quasi) with the approach of one group pre and post test design. The population in this study are patients with DM in Puskesmas Kedungmundu Semarang totaling 53 patients. A sample of 35 patients with sampling using purposive sampling technique. From the results of this study, the respondent data level of knowledge about diabetes mellitus before the media by Smart Book at Semarang City Health Center Kedungmundu average is 7.43. The level of knowledge about diabetes mellitus after by media Smart Book at Semarang City Health Center Kedungmundu average is 13. Media Smart Book is effective in increasing knowledge about the management of diabetes mellitus in patients with Diabetes Mellitus. Advice for patients should seek information about either of the diet DM mass media, the Internet, or follow counseling to increase knowledge in order to improve dietary adherence in patients with DM.